Fizicheskaia kul'tura kak osnova zdorovogo obraza zhizni - Pustovarova A. A. (Actual problems of education fundamentalization)
This article raises an extremely topical issue of physical activity and other important aspects of a healthy lifestyle. The facts described in the article are based on information from various textbooks on physical culture for higher education institutions, on research on this topic, described on various sites on the Internet, and on personal experience
Keywords: физическая культура; спорт; физическое воспитание; закаливание; physical education; sports; Physical culture; tempering